In vitro caecum fermentation and in vivo (Gallus gallus) of calcium delivery systems fabricated by desalted duck egg white peptides and chitosan oligosaccharide on gut health. (21st September 2021) - Zhao, Mengge; Ma, Aimin; He, Hui; Zhang, Xing; Jia, Lei; Hou, Tao
Abstract: As calcium supplements, two novel calcium delivery systems were prepared with desalted duck egg white peptides (DPs) and chitosan oligosaccharide (COS) by Amadori‐linkage and transglutaminase (TGase)‐induced reaction, with high calcium‐binding ability of promoting calcium absorption in vivo and in vitro . However, there are relatively few studies on the gut health of calcium delivery systems. In this experiment, in vitro caecum fermentation experiment and Gallus gallus intra amniotic feeding model were used to assess the gut health of calcium delivery systems and phytic acid. Results showed that two calcium delivery systems improved the microbial community structure by inhibiting the proliferation of Escherichia coli, and promoting the proliferation of Bifidobacterium and Lactobacillus . The addition of calcium delivery systems significantly increased short chain fatty acids (SCFAs) and improved the boundary membrane function of brush nutrients by significantly increasing villi structure, surface area, cup cell expansion and production of associated genes ( P < 0.05). Moreover, calcium delivery systems present significant reverse of the inhibitory effect of phytic acid on gut health through in vitro and in vivo experiments. This study suggested that DPs‐COS‐Ca systems were superior to the commercially available calcium supplement CaCO3 and had excellent calcium absorption and gut health regulating effects. Abstract : DPs‐COS Calcium delivery systems are highlighted to enhance gut health through in vitro cecum fermentation and intra‐amniotic administration ( Gallus gallus ).